2021
DOI: 10.1289/ehp8932
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Cadmium-Induced, Germline Mutations in a Long-Term Daphnia pulex Mutation-Accumulation Experiment

Abstract: Background: Germline mutations provide the raw material for all evolutionary processes and contribute to the occurrence of spontaneous human diseases and disorders. Yet despite the daily interaction of humans and other organisms with an increasing number of chemicals that are potentially mutagenic, precise measurements of chemically induced changes to the genome-wide rate and spectrum of germline mutation are lacking. Objectives: A large-scale Daphnia pule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…By necessity, we sampled only a subset (18%) of the genome, so our mutation rate may differ from the true average rate for the entire genome. Mutation rates are known to vary greatly across genomic features, and repetitive elements such as simple repeats and transposable elements are likely to mutate at a rate that differs from the genomic average due to factors, such as transcription level, chromatin status, and gene content [ 28 , 29 ]. Furthermore, it is important to note that we extracted DNA from whole individuals, rather than isolating tissues.…”
Section: Resultsmentioning
confidence: 99%
“…By necessity, we sampled only a subset (18%) of the genome, so our mutation rate may differ from the true average rate for the entire genome. Mutation rates are known to vary greatly across genomic features, and repetitive elements such as simple repeats and transposable elements are likely to mutate at a rate that differs from the genomic average due to factors, such as transcription level, chromatin status, and gene content [ 28 , 29 ]. Furthermore, it is important to note that we extracted DNA from whole individuals, rather than isolating tissues.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has observed that low-level Cd was a determinant of all-cause and CVD mortalities in the general American population . Cd, as a persistent toxic metal, was identified to have adverse effects on mitochondrial dysfunction, cell death, cell proliferation, and malignant transformation, induced by upregulation of BCL-2, MMP2, and MMP9. Additionally, long-term Cd exposure was found to have effects on DNA mutation and damage, and the associated genotoxicity may cause the development of cancer and result in cancer mortality. In the burden analysis, we assessed that Cd would be the top hazardous EDC that was associated with 334 300 deaths in populations aged 18 years and older. Cd was focused for its strong accumulation, toxicity, and widespread exposure pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation accumulation experiments in C. elegans and other organisms have determined that chemical exposures contribute to mutagenesis in the nuclear genome (61, 62). However, the role of chemicals in mtDNA mutagenesis is not well studied (63).…”
Section: Discussionmentioning
confidence: 99%